(untitled) (REMUNOM, 2023)
This work demonstrates, at first, notions, concepts and bases about the current technological scenario, leaning towards the specific scenario of robotics, which has great importance and current practical applicability. Subsequently, once such essential parameters have been established, this research turns into a more specific context, which is the application, delimitation and relevance of robotics inserted in the pedagogical context, called the educational robotics. Making use of extensive bibliographical research, this article aims to demonstrate how educational robotics is, undoubtedly, a remarkable mechanism to be managed in the didactic context, since it is capable of, at the same time, increasing the productivity of students and stimulating the development of unique and useful skills in the student and also professional context.